Mothers’ Psychological Well-Being through Islamic Coping Strategies in Raising Children with Special Needs - Alfiane Suci Setyasri; Khairunnisa Salsabila (Afkaruna: International Journal of Islamic Studies (AIJIS), 2026)
Raising a Child with Special Needs (CSN) presents a complex multidimensional burden, placing mothers at high risk of severe emotional exhaustion. This study aims to explore coping strategies and their impact on the psychological well-being of mothers raising CSN in Tanjung Kumbik Village, Pulau Tiga. Using a descriptive qualitative method with a case study design, data were collected through in-depth interviews and participatory observations of three mothers. The results indicate that mothers are highly vulnerable to emotional exhaustion and chronic sorrow due to heavy caregiving burdens. To cope, participants integrated problem-focused and emotion-focused coping, whose effectiveness was significantly moderated by maternal education levels and family social support. The main finding emphasizes the centrality of Islamic coping—through prayer, patience, trust in God (tawakkul), and perceiving the child as God’s trust—as a fundamental resolution for mothers’ psychological recovery. This spiritual strategy becomes a crucial anchor of resilience, especially for single mothers bearing double burdens without spousal support. It is concluded that spiritual approaches combined with an inclusive family ecological support system are essential in building the psychological well-being of mothers of CSN.